The Effect of Sport Vision Training on Visual Perception in Children with Intellectual Disability - Mahboobeh Emami; Alireza Bahramy; Vali Shiri (University of Tehran, 2018)
Children with intellectual disability experience many problems in theireveryday lives and educational issues. One of these important issues exists invisual perception. Therefore, the aim of the present study was to examine theeffect of sport vision training on visual perception of children withintellectual disability in Isfahan city. 30 children were selected fromeducable students with intellectual disability (7-11 years old) as the sampleand were randomly assigned to two groups (each group 15 subjects):experimental and control. Before the training, children with intellectualdisability underwent Wechsler IQ test and educable children entered thestudy. Also, before the training, the TVPS - II visual perception pretest wasadministered. Then, experimental group had their training for 8 weeks, 3sessions per week and 45 minutes each session. In the final stage, TVPS - IIvisual perception pretest was conducted. Based on the results of theMANCOVA analysis (with the control of pretest scores) sport visiontraining had an effect on the mean of all visual perception componentsexcept for form constancy test in the posttest (P<0.05). The results of thisstudy showed that sport vision training can improve the visual perception ofchildren with intellectual disability. Therefore, it is suggested that sportvision training is also used to treat and rehabilitate these children in thetreatment process.